Batch and Continuous Lactic Acid Production from Cassava by Streptococcus bovis - Razi, Fachrul; Yuwono, S D (Chemical Engineering Department, Syiah Kuala University, Banda Aceh, Indonesia, 2006)
Process variables were optimized for the production of lactic acid from cassava by Streptococcus bovis for batch and continuous fermentations. In the batch fermentation, maximum yield 82.5% and maximum lactic acid productivity 2.43 was achieved at 39 oC, pH 5.5 with 50 g/l cassava concentration. In the continuous fermentation maximum productivity lactic acid 1.25 g/l.h was obtained at dilution rate 0.05 /h.